2010
DOI: 10.1007/s11240-010-9763-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light-emitting diodes on growth and morphogenesis of upland cotton (Gossypium hirsutum L.) plantlets in vitro

Abstract: The objective of this study was to determine the effects of different light-emitting diode (LED) light sources on the growth of upland cotton (Gossypium hirsutum L.) plantlets. Shoot bud apex cuttings of upland cotton (1.0 cm) were transplanted on Murashige and Skoog (MS) basal medium supplemented with 0.1 mg/l 6-benzyladenine (BA) and 0.5 mg/l naphthalene acetic acid (NAA) and cultured in vitro for 45 days. They were exposed to 50 lmol m -2 s -1 photosynthetic photon flux (PPF) and a 12-h photoperiod under si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
124
4
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(152 citation statements)
references
References 53 publications
20
124
4
4
Order By: Relevance
“…Jao et al [18] reported that blue LEDs promote growth and increase chlorophyll content in Zantedeschia jucunda. The same effect was observed by Li et al [19,20] during in vitro culture of Gossypium hirsutum and Brassica campestris, respectively. Kim et al [9] and Moon et al [21] emphasized the role of blue light on chlorophyll formation and chloroplast development in their work with Chrysanthemum and Tripterospermum japonicum, respectively.…”
Section: Leds Affect Chlorophyll Contentsupporting
confidence: 82%
“…Jao et al [18] reported that blue LEDs promote growth and increase chlorophyll content in Zantedeschia jucunda. The same effect was observed by Li et al [19,20] during in vitro culture of Gossypium hirsutum and Brassica campestris, respectively. Kim et al [9] and Moon et al [21] emphasized the role of blue light on chlorophyll formation and chloroplast development in their work with Chrysanthemum and Tripterospermum japonicum, respectively.…”
Section: Leds Affect Chlorophyll Contentsupporting
confidence: 82%
“…Several studies have been made to optimize the micropropagation process, mainly related to culture medium composition (ABDULLATEEF et al, 2009). However, tissue culture environments might be improved by using new available light sources that might represent lower production costs, especially for seed potato production (SEABROOK, 2005;LI et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently developed light emission diodes (LEDs) have been pointed out by authors as potential sources of light for in-vitro environments cultivation. LEDs are characterized by specific wavelengths, small mass and volume, long useful life, low heating and highly efficient light generation process (60%), and do not contain mercury or other hazard element to the environment (YEH;CHUNG, 2009 ( NHUT et al, 2002), strawberry (ROCHA et al, 2010), cotton (LI et al, 2010), among others. This work aimed to optimize the in-vitro propagation of three potato cultivars, using new light sources in the culture environment.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable reduction in the length of hypocotyl was noticed when blue light proportion reached 10% . It is known that blue light is important for leaf expansion and it enhances the leaf area and biomass production [5,23]. In our study, combination C (50/30) was characterised by the greatest fresh mass of plants in the last week.…”
Section: Discussionmentioning
confidence: 54%